THE USE OF BOOK STORY IN TEACHING READING COMPREHENSION - Ivan Ferdiana Syarief; Yanuarti Apsari; Arsy Nastiti Karya Dewi (PROJECT (Professional Journal of English Education), 2020)
In general, students' difficulties in understanding of reading is in expressing the meaning and purpose of the reading. The researcher found these problem while conducting research at one of the Islamic Schools in class VIII  at SMP PLUS YPP DARUSSURUR CIMAHI. This study aims to improve the reading ability of students through English-language storybook media. This research used Classroom Action Research design which includes planning, action, observation, reflection or evaluation activities. The study was conducted SMP PLUS YPP DARUSSURUR CIMAHI. The sample of the research is class VIII C that contain of 26 students. The results showed that before treatment was given using the English-language storybook media, after reading comprehension learning using English-language book story at the first cycle the average value of reading comprehension skills of students increased  still in the medium category In cycle 1, the researcher discover that 70% or 18 out of 26 students got the score under KKM, and learning was done on the second cycle was found that 86.20% of the students or 25 out of 26 students got the score more than or equal to 70 related to the Minimum Mastery Criteria of reading comprehension ability of students experienced an increase in average value with a very high category. Keywords:   Reading, Media Story Books, CAR